Encapsulating Anti-Parasite Benzimidazole Drugs into Lipid-Coated Calcium Phosphate Nanoparticles to Efficiently Induce Skin Cancer Cell Apoptosis - Movahedi, Fatemeh; Gu, Wenyi; Soares, Christiane Pienna; Xu, Zhi Ping (Frontiers in Nanotechnology, 2021)
Benzimidazole (BMZ) family of anti-worm drugs has been now repurposed as anti-cancer drugs. However, offering a comprehensive reformulation method for these drugs is essential due to their hydrophobicity and low aqueous solubility. In this work, we developed a general approach to load typical BMZ drugs as tiny nanocrystals within lipid-coated calcium phosphate (LCP) nanoparticles. BMZ drug-loaded LCP nanoparticles demonstrated increased solubility in PBS by 100-200% and significantly enhanced the anti-cancer efficacy for treating B16F0 melanoma cells. These drug-LCP nanoparticles induced much more cancer cell apoptosis, generated much more reactive oxygen species (ROS) and inhibited Bcl-2 expression of cancer cells. Moreover, BMZ drug-loaded LCP nanoparticles caused morphological change and extension disruption of cancer cells, and significantly reduced migration activity, representing high possibility for inhibition of tumour dissemination and metastasis. Very advantageously, BMZ drug-loaded LCP nanoparticles did not show any obvious toxicity, Bcl-2 inhibition and morphological changes in HEK293T healthy cells. In conclusion, BMZ drug-incorporated LCP nanoformulations may be a valuable nanomedicine that is able to inhibit primary tumors and prevent tumor dissemination with minimum side effects on healthy cells and tissues.